The Right to Informational Self-Determination in the Context of Selected Judicial Decisions and Practical Background - Erdősová, Andrea (Public Governance, Administration and Finances Law Review, 2020)
It is essential to address in particular the comprehensive prevention of breaches of the right to informational self-determination and whether the persons concerned are aware that they “voluntarily agree” to pass on their identity information to third parties. It is alarming nowadays what amount of private data are available at their disposal for companies or private persons regarding other persons and how easy it seems to obtain this data. In today’s information age and the era of more advanced use of artificial intelligence, it will be more necessary than in the past to define what the individual intended, what he agreed with, and what he eventually approved as data privacy. In order to ensure the protection of the individual and his/her privacy, it is therefore necessary to respond to and refine the existing sources of law, especially to establish codes of ethics taking into account the modern technological and social development.